1996
DOI: 10.1037/0033-2909.119.3.422
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in aggression as a function of provocation: A meta-analysis.

Abstract: In this article, we meta-analytically examine experimental studies to assess the moderating effect of provocation on gender differences in aggression. Convergent evidence shows that, whereas unprovoked men are more aggressive than women, provocation markedly attenuates this gender difference. Gender differences in appraisals of provocation intensity and fear of danger from retaliation (but not negative affect) partially mediate the attenuating effect of provocation. However, they do not entirely account for it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

53
547
8
13

Year Published

1997
1997
2014
2014

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 719 publications
(621 citation statements)
references
References 158 publications
(196 reference statements)
53
547
8
13
Order By: Relevance
“…A side effect of this could be a greater propensity to identify with the victim. This result also seems to be in line with the general consensus in aggression research that female aggression is qualitatively different with at least less overt physical cruelty (Bettencourt & Miller, 1996;Eagly & Steffen, 1996). However, the influence of gender stereotypical socialization pro cesses has been discussed as one explanation for the reported differ ences, rather than biological differences between both sexes (Archer & Mehdikhani, 2003;Archer & Parker, 1994).…”
Section: Victim Identificationsupporting
confidence: 88%
“…A side effect of this could be a greater propensity to identify with the victim. This result also seems to be in line with the general consensus in aggression research that female aggression is qualitatively different with at least less overt physical cruelty (Bettencourt & Miller, 1996;Eagly & Steffen, 1996). However, the influence of gender stereotypical socialization pro cesses has been discussed as one explanation for the reported differ ences, rather than biological differences between both sexes (Archer & Mehdikhani, 2003;Archer & Parker, 1994).…”
Section: Victim Identificationsupporting
confidence: 88%
“…involving a conflict between maximizing personal versus collective interests ("mixed motive" games). Previous reviews examined sex differences in prosocial behaviors such as helping (Eagly, 2009;Eagly & Crowley, 1986) and heroism (S. W. Becker & Eagly, 2004), whereas other reviews have considered sex differences in competitive behaviors such as aggression (Archer, 2004(Archer, , 2009Bettencourt & Miller, 1996;Eagly & Steffen, 1986) and negotiations (Stuhlmacher & Walters, 1999;Walters et al, 1998). Yet, these results do not necessarily generalize to mixed-motive settings such as social dilemmas, which are psychologically unique because there is a tension between personal and collective interests in deciding whether people want to cooperate.…”
Section: Discussionmentioning
confidence: 99%
“…Unfair Treatment, Retaliation, and Self-Regulation 10 Given that prior research (Bettencourt & Miller, 1996) has suggested a link between gender and retaliation, we included gender as a covariate in all reported analyses. A gender main effect was obtained only in Studies 1 and 2: Men behave more retaliatorily than women.…”
Section: The Present Researchmentioning
confidence: 99%